The Work Realities of Professional Studio Musicians in the German Popular Music Recording Industry: Careers, Practices and Economic Situations - Herbst, Jan Peter (IASPM@journal, 2018)
Among the professional roles in the recording industry, studio musicians have received relatively little academic attention. The present study explores the work realities of professional studio musicians in Germany, one of the largest music industries in the world, and is based on interviews with six pop musicians; guitarists, bassists, keyboardists and drummers who are between 27 and 66 years old. The findings show how changes in the recording industry - most notably dwindling budgets, the rise of project studios and virtual collaboration - have affected working practices, skill requirements and business models. The findings indicate that in Germany it is hardly possible to make a living from studio work as a professional musician. This is true even for leading session players. Sinking fees and the lack of access to royalties pose a problem that is not tackled due to fierce competition and the risk of damaging one’s reputation.